Design and development of an aircraft type portable drone for surveillance and disaster management. Issue 3 (2nd July 2018) - Hasan, Kazi Mahmud; Newaz, S.H. Shah; Ahsan, Md. Shamim
Abstract : Purpose: The purpose of this paper is to demonstrate the development of an aircraft-type autonomous portable drone suitable for surveillance and disaster management. The drone is capable of flying at a maximum speed of 76 km/h. This portable drone comprises five distinct parts those are easily installable within several minutes and can be fit in a small portable kit. The drone consists of a ballistic recovery system, allowing the drone landing vertically. The integrated high-definition camera sends real-time video stream of desired area to the ground control station. In addition, the drone is capable of carrying ~1.8 kg of payload. Design/methodology/approach: In order to design and develop the portable drone, the authors sub-divided the research activities in six fundamental steps: survey of the current drone technologies, design the system architecture of the drone, simulation and modeling of various modules of the drone, development of various modules of the drone and their performance analysis, integration of various modules of the drone, and real-life performance analysis and finalization. Findings: Experimental results: the cruise speed of the drone was in the range between 45 and 62 km/h. The drone was capable of landing vertically using the ballistic recovery system attached with it. On the contrary, the drone can transmit real-time video to the ground control station and, thus, suitable for surveillance. The audio system of the drone can be used for announcement of emergency messages. The drone can carry 1.8 kg of payload and can be used during disaster management. The drone parts are installed within 10 min and fit in a small carrying box. Practical implications: The autonomous aircraft-type portable drone has a wide range of applications including surveillance, traffic jam monitoring and disaster management. Social implications: The cost of the cost-effective drone is within $700 and creates opportunities for the deployment in the least developed countries. Originality/value: The autonomous aircraft-type portable drone along with the ballistic recovery system were designed and developed by the authors using their won technology.